Hubungan Dukungan Sosial dengan Burnout Syndrome Pada Perawat Rumah Sakit RSUD Ibnu Sina Kabupaten Gresik - Ika Putri Novita Ningrum; Nugrahadi Dwi Pasca Budiono (SEHATI: Jurnal Kesehatan, 2025)
Burnout syndrome basically refers to the psychic withdrawal reaction of workers from the workplace, which includes frequent absences, distancing from the environment, being cynical, and even tending to no longer actively engage in work. The main purpose is to find out how the relationship between social support and burnout syndrome in nurses at Ibnu Sina Hospital, Gresik Regency. The study wast conducted cross-sectionally and quantitative. Total population involved was 300 nurses were assigned to the Medical Support Installation, Emergency Department (IGD), Inpatient Installation, and Outpatient Installation. The selected participants were randomized using (probability sampling) and Slovin's formula, resulting in a total of 198 nurses as respondents. Primary data were collected through the answers to the Social Provision Scale (SPS) questionnaire to directly assess the level of social support. The variables used were social support (independent), while burnout syndrome (dependent). Data analysis used nonparametric statistical testing (Spearman). The analysis has showed (p = 0.000), which indicates a significant relationship between social support and burnout syndrome in nurses at Ibnu Sina Hospital, Gresik Regency. Improvements should include giving awards, organizing family gatherings, workshops and seminars to strengthen positive social support between superiors, family members and even colleagues.